Search for Higgs boson pair production in the b¯bWW∗ decay mode at √s = 13 TeV with the ATLAS detector - Aaboud, M; Aad, G; Abbott, B; Ambroz, L; Artoni, G; Backes, M; Barr, A; Beresford, L; Bortoletto, D; Burr, J; Cooper-Sarkar, A; Frost, J; et al. (Springer Berlin Heidelberg, 2019)
A search for Higgs boson pair production in the b ¯bWW∗ decay mode is performed in the b ¯b`νqq final state using 36.1 fb−1 of proton-proton collision data at a centreof-mass energy of 13 TeV recorded with the ATLAS detector at the Large Hadron Collider. No evidence of events beyond the background expectation is found. Upper limits on the non-resonant pp → HH production cross section of 10 pb and on the resonant production cross section as a function of the HH invariant mass are obtained. Resonant production limits are set for scalar and spin-2 graviton hypotheses in the mass range 500 to 3000 GeV.